Evaluation of a Microporous Acoustic Liner Using Advanced Noise Control Fan Engine - Bharath Kenchappa; Kunigal Shivakumar (Applied Sciences)
A novel microstructurally controlled graded micro-porous material was developed and experimentally validated for noise reduction through a normal incidence impedance test. Extensive parametric studies were conducted to understand the influence of test specimen size, particle size, porosity, pore size, and its distribution on acoustic absorption and transmission loss. Based on previous research, this study evaluates the application of graded microporous material as an acoustic liner technology for aircraft turbomachine engines. The liner was fabricated in eight 45° segments, assembled in an aluminum test rig, and tested on NASA Glenn Research Center’s Advanced Noise Control Fan (ANCF) low-speed test bed for tonal and broadband noise. The study demonstrates that microstructurally controlled graded microporous material is very effective in dissipating sound energy with reductions in tonal sound pressure level (SPL) of 2 to 13 dB at blade passing frequencies and reductions in broadband SPL of about 2 to 3 dB for the shaft order greater than 40. While the proposed two-layer graded liner model successfully validated the concept, additional design optimization is needed to enhance performance further. This work highlights the potential of graded microporous material as next-generation acoustic liners, offering lightweight, efficient, and scalable aircraft engine noise reduction solutions.